The role of food shopping in later life - Pettigrew, Simone; Worrall, C.; Biagioni, Nicole; Talati, Zenobia; Jongenelis, Michelle (Elsevier BV, 2017)
By the time they reach retirement, individuals are typically highly experienced in sourcing food products and they have strong familiarity with food retailing environments. To investigate the ongoing role of food shopping in later life, the present study explored seniors’ attitudes to food shopping and their food-selection behaviours through the lens of their broader lifestyles. The aim was to provide insights of relevance to the development of future efforts to optimise seniors’ food shopping experiences and nutrition-related outcomes. Interviews were conducted with 75 Western Australians aged 60 + years to discuss food shopping in the context of their day-to-day lives. The sample was comprised mainly of women (n = 64) and the average age was 74 years. In general, food shopping was perceived to be a manageable but mundane part of life. The findings suggest that there has been an improvement in food retailing practices because many of the numerous areas of concern identified in previous research conducted in this geographical location a decade ago were not nominated as relevant by the interviewees. Instead, food-related issues reported to be most problematic included the difficulties associated with sourcing affordable food products that had been produced locally and that did not contain unacceptable food additives. Seniors’ food shopping concerns thus appear to have changed from functional aspects of the physical store environment to product attributes that reflect the increasing industrialisation of the food industry.